El Mapa fantasma. La epidemia que cambió la ciencia, las ciudades y el mundo moderno.: Libro de Steven Johnson - Flores-Rodríguez, Carlos E. (El Colegio de México, 2024)
The history of cities is also the history of their calamities and how they confront them. These cities embody a testimonial character that aids in understanding societal responses and meanings in the face of disruptive events such as those caused by epidemics. From a historiographical perspective, this book—a derivative of a thesis—focuses on Victorian London during the nineteenth-century cholera pandemic as its case study. It highlights two significant aspects: the ways in which cultures react to epidemics and the observation that, in response to fear or uncertainty, religion and science have consistently served as the two natural and unchanging responses to such crises, which often become conflated.